Yield efficiency evaluation of double slope solar stills connected with external spiral copper for potable water production - Al-Qadami E.H.H.; Ahsan A.; Abdurrasheed A.S.; Mustaffa Z.; Yusof K.W.; Takaijudin H.; Malek M.A. (Polish Society of Ecological Engineering (PTIE), 2023)
Among the key challenges of the 21st century, one can enumerate finding efficient technologies to enhance water purification. Seawater desalination had been identified as one of the main alternative solutions to increase the water resources on our planet and fulfill human demands. In this study, the yield performance of double slope solar still connected with the external spiral copper pipe as the water heater was investigated. Active and passive solar stills of equal evaporation area with covers (4 mm thickness and 45o slope in both sides) were manufactured using Perspex. Different parameters were investigated and compared during the experiment including yield and water quality indicators from both stills. The results showed a strong relationship between the water production rates and solar radiation intensities, water temperature as well as ambient temperature. Additionally, the water productivity from the active still was 20% higher compared to the passive one. Overall, the water quality parameters were within the acceptable limits, the rate of distillate water production was found to increase along with solar radiation intensity and water temperature. 2019 Polish Society of Ecological Engineering (PTIE).